Comparison of Difference in Hematologic and Hemodynamic Outcomes between Primary Total Knee Arthroplasty and Revision of Infected Total Knee Arthroplasty - Shon, Oog-Jin (Knee Surg Relat Res, 2016)
PURPOSE: This study is to identify preoperative cautions for revision of infected total knee arthroplasty (TKA) by understanding the differences in hematologic and hemodynamic changes between primary TKA and revision of infected TKA. MATERIALS AND METHODS: The study included 40 patients in each of the two groups: one group with patients who underwent TKA and the other group with patients who underwent revision of infected TKA. All patients matched for age and body mass index. The following data were compared between the groups: changes in blood pressure, variations in hemoglobin level, amount of postoperative blood loss and transfused blood, incidence of blood transfusion, white blood cell (WBC) count, albumin level, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and liver enzyme level. RESULTS: The hemoglobin levels, transfusion rate, and the amount of blood loss were significantly higher in the revision group (p=0.012). In both groups, CRP reached the highest level on the 3rd postoperative day but it was normalized 2 weeks postoperatively; however, the revision TKA group showed a greater tendency to normalization (p=0.029). There were significant differences between the groups in ESR, WBC, blood pressure, and changes in liver enzyme levels. CONCLUSIONS: Revision of infected TKA results in greater hemodynamic variations than primary TKA. Therefore, more efforts should be made to identify pre- and postoperative hemodynamic changes and hematologic status.